2014
DOI: 10.1021/jf403840c
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Esculin on Streptozotocin-Induced Diabetic Renal Damage in Mice

Abstract: The present study investigated the presence and mechanism of esculin-mediated renoprotection to assess its therapeutic potential. Esculin was orally administered at 20 mg/kg/day for 2 weeks to streptozotocin-induced diabetic mice, and its effects were compared with those of the vehicle in normal and diabetic mice. After oral administration of esculin to mice, the concentrations of esculin and esculetin in blood were 159.5 ± 29.8 and 9.7 ± 4.9 ng/mL at 30 min, respectively. Food and water intake were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 35 publications
(44 reference statements)
1
30
0
Order By: Relevance
“…Additionally, esculin showed wide pharmacological activities against different diseases, such as cognitive impairment in experimental diabetic nephropathy where it exhibited a strong anti-inflammatory activity marked by the suppressed p38 MAPK and JNK [142]. In models of streptozotocin-induced renal damage in diabetic mice [143], cold-restrained stress and pylorus ligation-induced ulcer [144], ethanol-induced gastric lesion [145], and LPS/D-galactosamine-induced acute liver injury [146], esculin significantly ameliorated inflammation evidenced by the suppressed TNF-α, IL-1β, and MPO. Li et al reported the protective role of esculin against LPS-induced macrophages and endotoxin shock in mice and NO production in vitro.…”
Section: Urolithin Amentioning
confidence: 99%
“…Additionally, esculin showed wide pharmacological activities against different diseases, such as cognitive impairment in experimental diabetic nephropathy where it exhibited a strong anti-inflammatory activity marked by the suppressed p38 MAPK and JNK [142]. In models of streptozotocin-induced renal damage in diabetic mice [143], cold-restrained stress and pylorus ligation-induced ulcer [144], ethanol-induced gastric lesion [145], and LPS/D-galactosamine-induced acute liver injury [146], esculin significantly ameliorated inflammation evidenced by the suppressed TNF-α, IL-1β, and MPO. Li et al reported the protective role of esculin against LPS-induced macrophages and endotoxin shock in mice and NO production in vitro.…”
Section: Urolithin Amentioning
confidence: 99%
“…Free radicals ROS and RNS could disrupt the physiological function of various tissues and possibly caused damage in the kidney. Kim et al [23] stated that the elevation of ROS and pro-inflammation cytokine levels played an important role in damaging glomeruli, tubules and blood vessels. Study results from Zafar et al [24] showed that diabetic rats (Rattus norvegicus) induced with a single-dose STZ injection on a 45 mg/kg body weight dose were found to have necrosis on their tubules, glomerulosclerosis, tubular atrophy, and a thickening of the glomerular membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin-induced renal cell damage is dependent on apoptosis induced by DNA damage [ 36 , 37 ]. Apoptosis in renal tubular cells has been observed in several kinds of renal disorders [ 38 ].…”
Section: Discussionmentioning
confidence: 99%